Analysis of the Electrical Conductivity Mechanisms and Energy Density of States in Ternary Chalcogenide Alloy S60-Se40-X-PbX - Muthana, Mohamed; Jasim , Kareem Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
We studied in this investigation the changes of the continuous conductivity of the electricity (σd.c) due to substituting part of Selenium with Lead in an S60-Se40-X-PbX alloy at weight ratios x = 0, 10, 20, and 30. Our investigation includes an examination of σd.c. mechanisms in chalcogenide semiconductors and governing the equations of the continuous D.C. electrical conductivity, and the application of these measured characteristics of S60-Se40-X-PbX glasses to assess Lead’s impact on extended, local, and Fermi energy state densities. Some procedures were applied to the materials, such as mixing, grinding, heating in quartz ampoules, placing them in a furnace, and heating them at 360°C. The results showed that electrical conduction occurs in three modes (conduction at high temperatures in the extended state, conduction at moderate temperatures in the local state, and conduction at low temperatures in the variable range hopping (VRH).